The role of global dietary transitions for safeguarding biodiversity. (September 2019) - Henry, Roslyn C.; Alexander, Peter; Rabin, Sam; Anthoni, Peter; Rounsevell, Mark D.A.; Arneth, Almut
Highlights: Diets low in animal products reduce agricultural expansion in biodiverse regions. Diets low in animal products reduce agricultural intensity in biodiverse regions. Lowering only ruminant products may not substantially reduce agricultural intensity. Land-use change effects on biodiversity will be taxon specific. Abstract: Diets lower in meat could reduce agricultural expansion and intensification thereby reducing biodiversity impacts. However, land use requirements, associated with alternate diets, in biodiverse regions across different taxa are not fully understood. We use a spatially explicit global food and land system model to address this gap. We quantify land-use change in locations important for biodiversity across taxa and find diets low in animal products reduce agricultural expansion and intensity in regions with high biodiversity. Reducing ruminant meat consumption alone however was not sufficient to reduce fertiliser and irrigation application in biodiverse locations. The results differed according to taxa, emphasising that land-use change effects on biodiversity will be taxon specific. The links shown between global meat consumption and agricultural expansion and intensification in the biodiverse regions of the world indicates the potential to help safeguard biodiverse natural ecosystems through dietary change.